The Use of Photo Elicitation to Explore the Impact of Social Work Student's Perceptions of Placements on Social Work Tutors and Consider Their Role in Practice Learning. Issue 3 (6th December 2020) - Caffrey, Bridget; Fruin, Helen; McHale, Julie Bailey; Ridgway, Victoria; Mchale, Rebecca Bailey
Abstract : The importance of learning in practice is acknowledged across health and social care professions. Social work students' experiences in practice settings has attracted some attention in academic literature, and the role and impact of the Practice Educator (PE) on student learning is increasingly recognised. However, there is a paucity of research examining the role of the social work tutor generally and particularly within practice learning settings. This paper presents a small-scale qualitative study exploring the impact of visual images produced by social work students reflecting their practice experiences on six social work tutors. Photo elicitation prompted discussion in a focus group setting which was subsequently thematically analysed, with four themes emerging. These were dichotomous relationships, difference and diversity, tutor brokerage skills, and student support. The images encouraged tutors to reflect upon the complexity of their relationship with social work students and question whether they were professionally equipped to support students in complex placement situations. In addition, the effectiveness of the curriculum in preparing social work students for practice was considered, particularly space afforded to students to reflect on practice learning in a safe environment. Opportunities to support SW tutors in their role and SW students in practice are deliberated.